On line separation of short-lived iodine isotopes - Achterberg, Erhard O. J.; De Aisenberg, E. Y.; Iglesias, F. C.; Jech, Alberto Estanislao; Moragues, Jaime Baudilio A.; Otero, O.; Pérez, K .L.; Proto-Otero, A. N.; Rossi, J. J.; Scheuer, W.; Suárez, J. F. (Herausgeber: H. Wagner, W. Walcher. Physikalisches Instituí der Universitat Marburg, 1970)
Fil: Achterberg, E. O. Comisión Nacional de Energía Atómica; Argentina